Effect of ropivacaine combined with pancuronium on neuromuscular transmission and effectiveness of neostigmine and 4-aminopyridine for blockade reversal: experimental study - Braga,Angélica de Fátima (2015)
BACKGROUND AND OBJECTIVES: The local anesthetic effects on neuromuscular junction and its influence on blockade produced by nondepolarizing neuromuscular blockers are still under-investigated; however, this interaction has been described in experimental studies and in humans. The aim of this study was to evaluate in vitro the interaction between ropivacaine and pancuronium, the influence on transmission and neuromuscular blockade, and the effectiveness of neostigmine and 4-aminopyridine to reverse the blockade. METHODS: Rats were divided into groups (n = 5) according to the study drug: ropivacaine (5 µg mL-1); pancuronium (2 µg mL-1); ropivacaine + pancuronium. Neostigmine and 4-aminopyridine were used at concentrations of 2 µg mL-1 and 20 µg mL-1, respectively. The effects of ropivacaine on membrane potential and miniature endplate potential, the amplitude of diaphragm responses before and 60 min after the addition of ropivacaine (degree of neuromuscular blockade with pancuronium and with the association of pancuronium-ropivacaine), and the effectiveness of neostigmine and 4-aminopyridine on neuromuscular block reversal were evaluated. RESULTS: Ropivacaine did not alter the amplitude of muscle response (the membrane potential), but decreased the frequency and amplitude of the miniature endplate potential. Pancuronium blockade was potentiated by ropivacaine, and partially and fully reversed by neostigmine and 4-aminopyridine, respectively. CONCLUSIONS: Ropivacaine increased the neuromuscular block produced by pancuronium. The complete antagonism with 4-aminopyridine suggests presynaptic action of ropivacaine.